Effects of Aluminum Substitution Configurations on the Catalytic Performance of Iron-Substituted Zeolite MFI for N2O Activation - MONTEJO-VALENCIA, BRIAN D. (LACCEI, 2024)
This study investigates the catalytic performance of iron-substituted zeolite MFI for N2O activation, focusing on the impact of aluminum substitution configurations on the catalytic performance of the zeolite. Our results indicate that the preferable site for the substitution of aluminum is in the T11-T2 position, with the strongest adsorption observed in the T11-T1 position. Furthermore, the most favorable activation of N2O was found to occur in the T7-T1 position. These findings provide crucial insights into the role of aluminum substitution in the design of highperformance zeolite catalysts for N2O activation. Overall, this study contributes to the advancement of efficient and sustainable strategies for the removal of N2O from industrial processes.